Applications to Elazığ Mental Hospital Emergency Department in 2021 years - Nulufer Kilic (Medicine Science, 2023)
In the present study, the purpose was to analyze the applications made to the emergency department of a mental disease hospital in eastern Turkey. The applications to the mental health and diseases hospital emergency department between 01.01.2021 and 01.01.2022 were examined in the study. The demographic data and psychiatric diagnoses of the patients were recorded. The data of 3712 people who applied to the emergency department of the hospital were analyzed. A total of 37.98% of these patients were hospitalized. Men constituted the majority both in all applications and in patients who were hospitalized for observation and treatment. The most frequent application to the emergency department of the hospital was the patients brought by law enforcement officers with a rate of 26.64%. In patients who were hospitalized, schizophrenia and other psychotic disorders were in first place with a rate of 30.35%, bipolar disorder and mood disorders were in second place with a rate of 29.29%, and a general psychiatric examination diagnosis was in third place with a rate of 11.91%. To know the demographic characteristics and clinical diagnoses of people who apply to psychiatric emergency departments in search of help is very important for mental health service planning and development. Larger studies with larger sample groups are needed to generalize and interpret the findings obtained in the present study. [Med-Science 2023; 12(4.000): 998-1003]